Evening Primrose Oil (Efamol) in the Treatment of Raynaud’s Phenomenon: A Double Blind Study - Belch, J J F; Shaw, B; O’Dowd, A; Saniabadi, A; Leiberman, P; Sturrock, R D; Forbes, C D (Thrombosis and Haemostasis, 1985)
Prostaglandin E1 (PGE1) and prostacyclin have been used in Raynaud’s phenomenon (RP) but are unstable and require intravenous administration. An alternative approach is to stimulate the body’s own PGE1 production via administration of the precursor essential fatty acid. We studied the effect of 12 capsules/day of evening primrose oil (EPO) on the manifestations of RP. 21 patients received a two week course of placebo, thereafter 11 received EPO for 8 weeks and 10 patients received placebo. As the weather worsened the placebo group experienced significantly more attacks than the EPO group. Visual analogue scales assessing the severity of attacks and coldness of hands improved in the EPO group. No changes were seen in either group in hand temperatures and cold challenge plethysmography. Blood tests showed some antiplatelet effects of the drug. In conclusion patients receiving EPO benefited symptomatically. This was not matched however by any change in objective assessment of blood flow, although changes in platelet behaviour and blood prostanoids were observed.
Keywords: Evening primrose oil; Essential fatty acids; Prostaglandins; Platelets; Raynaud’s phenomenon